From New Hire to Team Member: Key Methods for Overcoming Onboarding Barriers A case-study at Boeing Flight Operations Implementation Department - Giebat, Anton; Hållvik, Nathalie (My University, 2024)
Onboarding is the process by which new employees are integrated into the organiza- tion and develop the knowledge and skills needed to become effective team members. The quality of onboarding processes impacts time to productivity, job satisfaction, and cost, making it a critical business process. How to achieve the desired onboard- ing quality in environments of high business complexity has received little to no attention in previous research. This master thesis has contributed to this research gap by analyzing how to improve the quality and efficiency of an onboarding process through a qualitative case study. The case study investigated the Case Company’s current onboarding processes and identified possible barriers to learning. Lastly, the study analyzed and presented improvement initiatives to increase onboarding quality and efficiency. The studied department at the Case Company implements in-house developed IT systems for airlines globally, mainly employing engineers with higher degrees. Challenges regarding time to productivity and strain on mentors have been experienced within their onboarding processes. Both the talent program onboarding and regular onboarding process are built upon a mentorship program accompanied by courses. The study has identified and highlighted current barriers within the areas of business complexity, process variation, courses, mentorship, and socializa- tion. With business complexity being the most significant barrier to becoming a productive team member, process variation impacts the possibilities of continuously developing the process, and socialization is one of the Case Company’s strengths compared to previous research. Based on the identified barriers, some of the rec- ommended initiatives for the Case Company include increased formalization of the onboarding process, striving for a mentee-centered learning approach, and involv- ing new employees in customer interactions early. Firstly, a formalized onboarding process aims to provide similar conditions for success to all mentors and mentees by balancing standardization and adaptability. Secondly, Mentee-centered learn- ing focuses on planning learning around each mentee. This could be done through increased digital course offerings complemented with workshops rather than pre- scheduled physical courses. Finally, customer interactions have been identified as one of the main experiences facilitating increased learning within business complex- ity. The case study further shows the impact organizational culture can have on socialization.
Keywords: Onboarding Process; Onboarding Barriers; Mentorship; Process Improvement; Business Complexity; Socialization